From Guns to Mental Health and Accountability: Decoding Media Narratives and Audience Reactions in Public Mass Shootings - Maurice N. Emelu; Brent Brossmann (Journalism and Media)
Public mass shootings pose a critical safety challenge in the U.S. This study investigates how media framing relates to public online engagement, focusing on gun regulation, mental health, and individual and political accountability across five major TV networks: ABC, CNN, Fox News, MSNBC, and NBC. Using a mixed-methods approach, the research analyzes 678 news reports and 7605 audience comments. Findings reveal significant differences in audience engagement based on framing, and in key variables show audiences taking opposite positions to their news network’s narratives. ABC, CNN, and NBC’s thematic framing, highlighting systemic failures, elicits more balanced responses, whereas Fox News and MSNBC’s episodic framing, emphasizing individual or political accountability, correlates with polarized reactions. This research extends media framing theories by showing how episodic framing reduces support for systemic reforms, emphasizing personal responsibility. The study offers crucial insights for scholars, policymakers, and journalists on media’s role in shaping public discourse on gun violence.